2017
DOI: 10.1038/srep44605
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA roles in signalling during lactation: an insight from differential expression, time course and pathway analyses of deep sequence data

Abstract: The study examined microRNA (miRNA) expression and regulatory patterns during an entire bovine lactation cycle. Total RNA from milk fat samples collected at the lactogenesis (LAC, day1 [D1] and D7), galactopoiesis (GAL, D30, D70, D130, D170 and D230) and involution (INV, D290 and when milk production dropped to 5 kg/day) stages from 9 cows was used for miRNA sequencing. A total of 475 known and 238 novel miRNAs were identified. Fifteen abundantly expressed miRNAs across lactation stages play regulatory roles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 86 publications
(119 reference statements)
6
82
0
2
Order By: Relevance
“…Le Guillou et al [61] identify 167 novel miRNAs in the bovine MG, many of which were also detected in mouse MG. Analysing three milk fractions (fat, whey and cells) and mammary gland tissues, we reported 210, 200 and 249 known and 33, 31 and 36 novel miRNAs in milk fat, whey and cells, respectively, and 321 known and 176 novel miRNAs in mammary gland tissues [62]. Deep sequencing the milk fat across the lactation curve, we also identified a total of 475 known and 238 novel miRNAs [63].…”
Section: Cattlementioning
confidence: 99%
See 3 more Smart Citations
“…Le Guillou et al [61] identify 167 novel miRNAs in the bovine MG, many of which were also detected in mouse MG. Analysing three milk fractions (fat, whey and cells) and mammary gland tissues, we reported 210, 200 and 249 known and 33, 31 and 36 novel miRNAs in milk fat, whey and cells, respectively, and 321 known and 176 novel miRNAs in mammary gland tissues [62]. Deep sequencing the milk fat across the lactation curve, we also identified a total of 475 known and 238 novel miRNAs [63].…”
Section: Cattlementioning
confidence: 99%
“…Li et al [50] in the dry period (30 days prepartum) compared to early lactation period (7 days postpartum) and one upregulated miRNA (miR-31) in early lactation compared to the dry period. Previously, we examined miRNA expression pattern during a lactation cycle to explore it regulatory mechanisms during lactation using milk fat as input tissue for sampling [63]. In a previous investigation, we have shown that milk fat miRNA transcriptome closely resemble the miRNome of MG tissue [62].…”
Section: Temporal and Spatial Expression Of Micrornasmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, De Vliegher et al [85] used miRbase [86] and UNAFold [87] for miRNA annotation and discovery in bovine mammary gland tissues while Peng et al [88] used miRbase [86] and RNAfold [89] for these purposes in porcine mammary glands. In our own studies, miRbase [86] and mirDeep2 [74] were used to identify miRNAs in various tissues including bovine mammary gland tissues [90], milk fat [90][91][92], milk whey and cells [90].…”
Section: Tools For Mirna Identiicationmentioning
confidence: 99%